The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1145/2645643
|View full text |Cite
|
Sign up to set email alerts
|

A Sketch-Based Approach for Interactive Organization of Video Clips

Abstract: With the rapid growth of video resources, techniques for efficient organization of video clips are becoming appealing in the multimedia domain. In this article, a sketch-based approach is proposed to intuitively organize video clips by: (1) enhancing their narrations using sketch annotations and (2) structurizing the organization process by gesture-based free-form sketching on touch devices. There are two main contributions of this work. The first is a sketch graph, a novel representation for the narrative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…We conducted a study to evaluate VideoMap, which demonstrated how the system can facilitate exploration of video content and significantly reduce browsing time needed to understand and find events of interest. Firstly, we compared VideoMap to two state-of-the-art video visualization and interaction methods: Storyline [22] and the Sketch Graph method [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a study to evaluate VideoMap, which demonstrated how the system can facilitate exploration of video content and significantly reduce browsing time needed to understand and find events of interest. Firstly, we compared VideoMap to two state-of-the-art video visualization and interaction methods: Storyline [22] and the Sketch Graph method [24].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the traditional interaction method of using markers on a timeline to navigate through video content [23], new natural sketch-based interaction has been used in video authoring [12,24] by operating on a sketch summary. Visual feedback is also important for efficient interaction, following user preferences [25].…”
Section: Related Workmentioning
confidence: 99%
“…image, video, threedimensional (3D) model) has become an active research area. [22][23][24] Sketch-based retrieval methods allow users to submit a sketch drawing illustrating their search intent. Such a way of user query intent expression provides users much freedom to specify and clarify their search need.…”
Section: Related Workmentioning
confidence: 99%
“…Hu and Collomosse 6 adopted a Bag-of-Visual Words (BoVW) approach, incorporating Gradient Field HOG (GF-HOG) descriptor for SBIR. Liu et al 24 proposed an interactive sketch-based interface to organize video clips, enabling common users to easily draw simple sketches, and these sketches are automatically converted from keyframes of videos. Eitz et al 22 proposed a new sketch-based 3D model retrieval system based on bag-of-features framework.…”
Section: Related Workmentioning
confidence: 99%
“…Due to less information stored in line drawings when compared to the color photographs, the usage of line drawings in intelligent process of visual media, including the retrieval and re-use of images [9,10], videos [11,12], 3D graphical models [13,14,15] and conceptual design in industry [16,17], has attracted considerable attention recently. The reader is referred to [5] for a survey.…”
Section: Related Workmentioning
confidence: 99%